KOMPONEN KIMIA DAN FISIK ABU SEKAM PADI SEBAGAI SCM UNTUK PEMBUATAN KOMPOSIT SEMEN - . Bakri (PERENNIAL, 2009)
This research aimed to determine chemical and physical component of rice husk ash as supplementing cement material to manufacture cement composite products. Charcoal of rice husk ash obtained by burning rice husk conventionally in kiln drum and burned again in furnace 1400 Barnsted Thermolyne Type at temperature 600o C for 2 hours. Analysis of chemical and physical component refer to SNI 15-2049-2004. Major chemical compound of rice husk ash was 72.28 % of silica and 21.43 of LOI. Density of rice husk ash was 760 kg/m3. Key words: SCM, rice husk ash, chemical and physical component, cemet composite